Impact of Different Training Modalities on Molecular Alterations in Skeletal Muscle of Patients With Heart Failure With Preserved Ejection Fraction: A Substudy of the OptimEx Trial. (6th October 2022) - Winzer, Ephraim B.; Augstein, Antje; Schauer, Antje; Mueller, Stephan; Fischer-Schaepmann, Tina; Goto, Keita; Hommel, Jennifer; van Craenenbroeck, Emeline M.; Wisløff, Ulrik; Pieske, Burkert; Halle, Martin; Linke, Axel; et al.
Abstract : Background: Exercise intolerance is a cardinal feature of heart failure with preserved ejection fraction and so far exercise training (ET) is the most effective treatment. Since the improvement in exercise capacity is only weakly associated with changes in diastolic function other mechanisms, like changes in the skeletal muscle, contribute to improvement in peak oxygen consumption. The aim of the present study was to analyze molecular changes in skeletal muscle of patients with heart failure with preserved ejection fraction performing different ET modalities. Methods: Skeletal muscle biopsies were taken at study begin and after 3 and 12 months from patients with heart failure with preserved ejection fraction randomized either into a control group (guideline based advice for ET), a high-intensity interval training group (HIIT) or a moderate continuous training group. The first 3 months of ET were supervised in-hospital followed by 9 months home-based ET. Protein and mRNA expression of atrophy-related proteins, enzyme activities of enzymes linked to energy metabolism and satellite cells (SCs) were quantified. Results: Exercise capacity improved 3 months after moderate continuous exercise training and HIIT. This beneficial effect was lost after 12 months. HIIT mainly improved markers of energy metabolism and the amount and function of SC, with minor changes in markers for muscle atrophy. Only slight changes were observed after moderate continuous exercise training. The molecular changes were no longer detectable after 12 months. Conclusions: Despite similar improvements in exercise capacity by HIIT and moderate continuous exercise training after 3 months, only HIIT altered proteins related to energy metabolism and amount/function of SC. These effects were lost after switching from in-hospital to at-home-based ET. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02078947.